Struggle for the Street Social Networks and the Struggle for Civil Rights in Pittsburgh. - Klanderud, Jessica D. (Justice, Power, and Politics Series., 2023)
"In Struggle for the Street, Jessica Klanderud documents the development of class-based visions of political, social, and economic equality in Pittsburgh's African American community between World War I and the early 1970s. By placing the street at the center of historical change over time, Klanderud emphasizes how middle-class and working-class African Americans struggled over the appropriate uses and dominant meanings of street spaces in their neighborhoods as they collectively struggled to define equality"--